Cuerpos estructurales resilientes sistema de nivelación adaptable para viviendas modulares anfibias sobre cuerpos de agua cambiante (2021)
This research work focuses on the proposal for the implementation of resilient structural bodies adaptable leveling system for amphibious modular homes on changing bodies of water, this proposal is aimed at offering a viable solution in case of floods in the homes that are on the banks of rivers and / or areas of low tide and that is also composed of irregular terrain.